All carbon hybrid N-doped carbon dots/carbon nanotube structures as an efficient catalyst for the oxygen reduction reaction. Issue 21 (30th March 2021) - Nguyen, Anh Thi Nguyet; Shim, Jun Ho
Abstract : The ORR measurements showed that the CD(ED)/CNT catalyst was superior to CD(EG)/CNT and CD(EA)/CNT. They even surpassed the activity of commercial Pt/C in terms of durability, Tafel slope, and MeOH tolerance. Abstract : This paper reports the facile and scalable synthesis of hybrid N-doped carbon quantum dots/multi-walled carbon nanotube (CD/CNT) composites, which are efficient alternative catalysts for the oxygen reduction reaction (ORR) in fuel cells. The N-doped CDs for large-scale production were obtained within 5 minutes via a one-step polyol process using ethylenediamine (ED) in the presence of hydrogen peroxide as an oxidizing agent. For comparison, different CDs were also prepared using ethylene glycol (EG) and ethanolamine (EA) in the same manner. Physicochemical characterization suggested the successful formation of a CD(ED)/CNT hybrid without individual CD(ED)s and CNTs. The N-doped CD(ED)/CNT catalyst exhibited excellent electrocatalytic activity in an alkaline solution compared to other composites (CD(EG)/CNT and CD(EA)/CNT). The Tafel slope (−60.9 mV dec −1 ) and durability (∼9.1% decay over 10 h) for CD(ED)/CNT were superior to high-performance Pt/C catalysts. The electrochemical double-layer capacitance on the CD(ED)/CNT hybrid showed apparent improvement of the active surface area because of N-doping and highly decorated CDs on the CNT wall. These results provide an innovative approach for the potential application of all carbon hybrid structures in electrocatalysis.